Sport and Physics - Leopold Mathelitsch (Karolinum Press, 2017)
The combination of sport and physics oﬀers several attractive ingredients for teaching physics, at primary, secondary, as well as university level. These cover topics like interdisciplinary teaching, sports activities as physics experiments, video analysis or modeling. A variety of examples are presented that should act as stimulus, accompanied by a list of references that should support the implementation of sport topics into physics teaching.